Surfing the net for software engineering notes. - Doernhoefer, Mark (Software engineering notes.)
Building real-time applications can be one of the most difficult jobs facing today's software engineers. With all the talk about Web services and Web based applications we sometimes forget that there is a large community of practice engaged in the construction of hard real-time systems. Real-time software engineering has been around for several decades. Typical real-time applications can be found in the areas of communications, avionics, process control, and other specialized applications such as signaling and switching systems.